OPTIMASI USAHATANI BERKELANJUTAN PADA RUMAHTANGGA TANI LOKAL DAN PENDATANG DI DAERAH LAHAN PASANG SURUT KABUPATEN KAPUAS - , JHON WARDIE, SP,MP; , Dr. Ir. Slamet Hartono, MSc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aimed to: (1) analyze the level of sustainability of farming, (2) analyze the optimal resource allocation of farm households, (3) find the resources to be limiting factors or the main constraints, and (4) analyze the effect of changing resource constraints of livestock, input prices, output prices and farm technology on optimal resource allocation and maximum income for farm households in tidal swamps area. The research was conducted in Kapuas District and sampling is purposive sampling by selecting each 50 local farm households and 50 non local farm households in tidal swamps area. Measurement sustainability of farming on farm households in flood type A and B using the Likert scale with scoring indicator of sustainability of farming. Measurement optimization using linear programming model. Management of land farming and yards organized with surjan system, the plants arranged in a pattern of farming. The pattern of farming on the local farm households in the land farming are local rice, local rice + rambutan, local rice + fruits1, local rice + fruits2, local rice + vegetables1, local rice + non local rice + banana, and in yards is fruits3 pattern. While the non local farm households in the land farming are local rice, local rice + cassava, local rice + vegetables2, local rice + rubber, and in yards are local rice, rambutan, rubber, fruits3, fruits4, and fruits5. In addition to farming, farm households also raise cattle, goats, chickens and ducks. Level of sustainability of farming on the non local farm households categorized highly sustainable, while at the local farm households categorized quite sustainable. Level of sustainability of farming on farm households in the type A and B are both categorized quite sustainable, confirmed there was a statistically significant difference. Optimal farming pattern on the local farm households are the pattern II (local rice + rambutan) and pattern fruits3 (banana + mango) with income (after consumption) maximum of Rp. 6,712,767. While the pattern of optimal farming on the non local farm households are the pattern IV (local rice + rubber) and pattern III (rubber) with income (after consumption) maximum of Rp. 5,839,699. Land and capital are scarce resources (active) to become the limiting factor in farming activities, while labor is not scarce resources (passive). Increase the number of livestock, input prices, output prices and farm technology may result in increased farm households income and the increasing amount of use of internal inputs (organic fertilizer) replaces the use of external inputs (inorganic fertilizer).